2023
DOI: 10.1186/s12876-023-02749-9
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of nomograms for predicting overall survival and cancer-specific survival in elderly patients with locally advanced gastric cancer: a population-based study

Abstract: Objective To evaluate the multiple factors influencing the survival of elderly patients with locally advanced gastric cancer (LAGC) and develop and validate the novel nomograms for predicting the survival. Methods The clinical features of patients treated between 2000 and 2018 were collected and collated from the Surveillance, Epidemiology, and End Results (SEER) database and three medical centres in China, and the patients were randomly divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Sun et al. ( 48 ) explored various factors affecting the survival of elderly patients with locally advanced GC. Statistical analysis showed that the T/N/M stages were independent prognostic factors for OS and CSS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sun et al. ( 48 ) explored various factors affecting the survival of elderly patients with locally advanced GC. Statistical analysis showed that the T/N/M stages were independent prognostic factors for OS and CSS.…”
Section: Discussionmentioning
confidence: 99%
“…Zhong et al (47) found that TNM staging and radical surgery were independent prognostic factors affecting OS in young GC patients. Sun et al (48) explored various factors affecting the survival of elderly patients with locally advanced GC. Statistical analysis showed that the T/N/M stages were independent prognostic factors for OS and CSS.…”
mentioning
confidence: 99%